Effects of copper (Cu2+) on chlorophyll, proline, protein, and abscisic acid level of sunflower (Helianthus annuus L.) seedlings - Zengin K, F. (Amer Soc Biochemistry Molecular Biology Inc, 2005)
[Abstract Not Available]